Pakikipagkapwa as Public Ethics: Religion, Governance, and the Mediation of Compassion in Filipino Society - Cristabel F. Tiangco; Vladimer B. Kobayashi; Purisima P. Panlilio; Remi E. De Leon; Angela D. Carreon; Maria Margarita R. Lavides (Religion and Policy Journal, 2026)
Research Problem: This article examines how pakikipagkapwa, a central Filipino value grounded in the recognition of the other as a shared self, operates beyond interpersonal relations as a public ethical framework. Although pakikipagkapwa has often been discussed as a cultural and psychological value, its relevance to religion, governance, public policy, and crisis response remains insufficiently examined. This gap is important because compassion and solidarity require not only personal virtue but also institutional, technological, and policy conditions that enable their public expression. Research Purposes: This article aims to analyze the moderators, mediums, and enablers that shape the development, circulation, and public expression of pakikipagkapwa. It also seeks to explain how this value informs compassion, civic responsibility, solidarity, crisis response, and ethical governance in Filipino society. Research Methods: This study uses a qualitative exploratory approach based on secondary analysis of the digital scraping study conducted by Kobayashi et al. (2024). The original data consisted of 641,727 texts collected from seven online sources: YouTube, X, Subreddit Philippines, PinoyExchange, Philippines Expats Forum, Expat.com, and Skyscraper City. The analysis focuses on word clusters classified as moderators, mediums, and enablers of pakikipagkapwa. Results and Discussion: The findings show that families, religious organizations, educational institutions, and public personalities moderate pakikipagkapwa by shaping moral formation, prosocial behavior, and civic orientation. Technology, government, mass media, and media-associated civil society organizations function as mediums that communicate and mobilize compassion into public action. Weather conditions, natural disasters, and crises enable pakikipagkapwa by activating empathy, mutual aid, social cohesion, and collective responsibility. The article also notes that poverty, safe environment, functionality, and gender role did not emerge clearly in the model, revealing the limits of online discourse-based analysis. Research Implications and Contributions: This article contributes to religion, governance, and public policy studies by positioning pakikipagkapwa as a normative resource for compassionate governance, crisis response, public responsibility, and ethical public life.